2022
DOI: 10.3839/jabc.2022.056
|View full text |Cite
|
Sign up to set email alerts
|

Comparative untargeted metabolomic analysis of Korean soybean four varieties (Glycine max (L.) Merr.) based on liquid chromatography mass spectrometry

Abstract: Soybean is a crop with high-quality of protein and oil, and it is one of the most widely used genetically modified (GM) crops in the world today. In South Korea, Kwangan is the most utilized variety as a parental line for GM soybean development. In this study, untargeted LC-MS metabolomic approaches were used to compare metabolite profiles of Kwangan and three other commercial varieties cultivated in Gunwi and Jeonju in 2020 year. Metabolomic studies revealed that the 4 soybean varieties were distinct based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…3 are shown in Table 1. In particular, except for tryptophan, the remaining metabolites had VIP values of over 1.0 [40], which showed that they signi cantly promoted the difference between the two groups.…”
Section: Metabolite Analysis Using Uplc-q-tof Msmentioning
confidence: 94%
“…3 are shown in Table 1. In particular, except for tryptophan, the remaining metabolites had VIP values of over 1.0 [40], which showed that they signi cantly promoted the difference between the two groups.…”
Section: Metabolite Analysis Using Uplc-q-tof Msmentioning
confidence: 94%